A taxonomic revision of the genus Eperua (Leguminosae, Detarioideae, Detarieae) - Fortes, Elenice A.; Reis, Ilka P. Dos; Steege, Hans Ter; Aymard, Gerardo; Secco, Ricardo De S.; Martins-Da-Silva, Regina Célia V.; Mansano, Vidal F. (Phytotaxa, 2023)
We present a comprehensive taxonomic revision of the tree genus Eperua, encompassing several significant findings. We identify and recognize a total of 19 species (including two new species described herein; E. froesii, E. reddeniae), as well as five subspecies (including one new, E. grandiflora subsp. ciliata), and six varieties (including one new, E. glabriflora var. gynopubescens). We also propose the synonymization of E. praesagata with E. glabra due to the absence of discernible morphological differences, which is supported by molecular data. In addition to these novelties, our revision offers an updated key, illustrations, photos, and maps. Detailed taxonomic comments are provided, discussing morphological similarities and differences between taxa. Furthermore, comprehensive information is provided for each species, including data on phenology, distribution, habitat, conservation status, and vernacular names. Eperua froesii is being described from specimens collected more than 50 years ago, while E. reddeniae and E. grandiflora subsp. ciliata from specimens collected recently (2004–2006). This emphasizes the critical role of herbarium collections in biodiversity discovery and underscores the significance of historical specimens. Our taxonomic comments add to Cowan’s (1975) revision, in which the author concentrated on listing characteristics considered advanced and less advanced, while here we focus on morphological similarities and differences between taxa. In conclusion, this new taxonomic revision significantly enhances our knowledge of the genus Eperua and provides a basis for further research in evolution, ecology, and phytochemistry.